Vertical stratification of P pools in subtropical plantation soils under fertilization and dry–season irrigation: multiomics regulatory strategies - Zhang, Shitao; Mo, Yang; Yang, Jincheng; Chen, Xiaoshan; Gao, Meiling; Su, Yan; Qiu, Quan; He, Qian (Frontiers in Microbiology, 2026)
The rapid expansion of fast-growing plantations in subtropical regions is closely linked to silvicultural practices, however, improper practices often lead to soil acidification and reduced nutrient bioavailability. Phosphorus (P), one of the most critical elements for plantation tree growth, shows complex spatial distribution patterns in soil that are influenced by multiple factors, directly affecting plantation productivity. This study investigated the effects of long-term fertilization and dry-season irrigation on the vertical distribution of phosphorus in an 8-year-old subtropical Eucalyptus plantation. This study employed stratified sampling (0–30 cm topsoil, 30–60 cm subsoil, 60–90 cm substratum) during dry seasons, coupled with metagenomics, metabolomics, and environmental factor analysis, to reveal vertical phosphorus cycling patterns and multiomics regulatory networks. Key findings: (1) Fertilization and dry-season irrigation had a limited influence on labile phosphorus and the diversity of P-cycling microorganisms. The topsoil presented significantly greater P availability than did the subsoil, manifested as elevated acid phosphatase activity (ACP), significant enrichment of the tryptophan metabolic pathway, and greater microbial diversity. (2) pH and the C:P ratio represent critical factors of vertical stratification in soil P cycling. Under acidic conditions, topsoil microorganisms facilitate P release via diverse metabolic pathways, whereas oligotrophic constraints in the substratum limit enzymatic activities. (3) Potential cross-stratum microbial functional coordination exists in acidic soil P cycling, with linkages to tryptophan metabolism and polyphosphate, synthesis/degradation. Our study provides theoretical multiomics insights for optimizing the management of soil P pools in subtropical plantations under fertilization and dry-season irrigation.